A multi-level study of servant leadership on creativity: The roles of self-efficacy and power distance. Issue 5 (3rd July 2017) - Yang, Jin; Liu, Hefu; Gu, Jibao
Abstract : Purpose: The purpose of this paper is to explore the influencing mechanism of servant leadership on employee and team creativity based on efficacy theory. Specifically, the study intends to develop a model of efficacy beliefs that mediates the relationships between servant leadership, employee creativity, and team creativity at different levels. The study also aims to investigate the moderating effects of team power distance on the relationships between servant leadership, creative self-efficacy, and team efficacy at both individual and team levels. Design/methodology/approach: Servant leadership, employee creativity, creative self-efficacy, team creativity, team efficacy, and team power distance were assessed in an empirical study based on a sample of 466 employees and 83 team leaders from 11 banks in China. Findings: From efficacy theory perspective, this paper finds that servant leadership promotes employee creative self-efficacy and team efficacy, which enables the simultaneous promotion of employee creativity and team creativity. Team power distance also moderates the relationship between servant leadership and team efficacy. Practical implications: The results suggest that it is important to encourage managers to engage in servant leader behaviors, which is conductive to enhancing employees' self-efficacy beliefs and thereby improving creative outcomes of employees. The results are also helpful for managers to enhance their understanding of the differences in cultural values in management behavior and the effects of behavior on team efficacy. Originality/value: The research findings provide a significant contribution to the literature in that it shows self-efficacy as a crucial mediating mechanism through which servant leadership influences creativity at individual and team levels. Moreover, the findings support the view that power distance is an important contextual factor that affects the influencing mechanism of servant leadership on team creativity. Furthermore, this paper is one of the few studies answering the call to examine the effect of leadership at multiple levels.